Technical and tactical performance in professional female futsal players: a descriptive analysis depending on teams level and playing group - Villarejo García, D. H.; González-Fernández, F. T.; Rico-González, M.; Pino-Ortega, J.; Del Rosso, S.; Puche-Ortuño, D. (International Journal of Performance Analysis in Sport, 2025)
Among the many factors that can affect women`s futsal performance, technical and tactical actions can obscure relevant game data, even affecting specialists in both the programming and design of training tasks. This study describes the technical and tactical actions in elite futsal teams, analysing performance measures according to the playing group and team ranking level. One hundred and twenty-eight games from an Elite League in the 2020/2021 season were observed. The variables analysed were grouped into three groups: "Goals and Rules", "Attack" and "Defence". The two-way mixed ANOVA analysis revealed significant effects in attacking variables such as Shots to the Post (STP) variable (F1.2 =19.13, p = .04, ?2 = .90) and Throw-in For (TIF) variable (F1.2 =75.00, p = .01, ?2 = .97), as well as in defensive Interception (INT) variable (F2.4 = 8.74, p = .03, ?2 = .81) in the playing group condition. This study observed how consistently those teams positioned at the top developed a higher goal average compared to those teams further down the ranking. The study highlights the significance of the offensive part and the number of goals in the game system and how achieving good numbers in this area can influence. Coaches and athletes can use the intraclass correlation coefficient to demonstrate how specific technical and tactical actions impact performance.